MENINGKATKAN HASIL BELAJAR SOSIOLOGI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN BERBASIS MASALAH PADA KELAS XII IPS 4 DI SMA NEGERI 1 BARABAI - Muzairin Muzairin (JURNAL SOCIUS, 2014)
The aim of research was to describe the use of Problem Based Learning model to increase Sociology learning achievement at grade XII IPS 4 students of SMAN 1 Barabai. The method used for this research was class action research with qualitative approach that focused on efforts to describe deeply anyhing related to the increasing of students’ interest and learning achievement. By this qualitative analysis, the researcher concerned to main problems especially students’ interest and learning achievement in Sociology, so that the problems can be identified and analysed which then the researcher had consideration to find alternative solutions. The data analysis result showed that the use of Problem Based Learning model can increase learning achievement at grade XII IPS 4 students of SMAN 1 Barabai. Classically, the increasing point is 7,25% in the first cycle, and 25% in the second one.            Key words: Learning achievement, Problem Based Learning,and Sociology